A randomized study of high-dose pineal hormone melatonin alone versus high-dose melatonin plus low-dose angiotensin-(1-7) in untreatable advanced cancer patients - Lissoni, Paolo (2021)
Fil: Lissoni, Paolo. Institute of Biological Medicine; Italia